Evaluation of Job Benefits of Members of the American Agricultural Editors Association - Cfifford W. Scherer; Paul Yarbrough; Jane Peterson (Journal of Applied Communications, 1980)
The Communication Clinic Committee of the American Agricultural Editors Association (AAEA), in cooperation with the Iowa State University Department of Journalism and Mass Communication, surveyed AAEA members to determine salaries, fringe benefits, and satisfaction with benefits.